2012
DOI: 10.1044/1092-4388(2011/11-0143)
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Family Environment to Pediatric Cochlear Implant Users' Speech and Language Outcomes: Some Preliminary Findings

Abstract: Purpose To evaluate the family environments of children with cochlear implants and to examine relationships between family environment and post-implant language development and executive function. Method Forty-five families of children with cochlear implants completed a self-report family environment questionnaire (FES) and an inventory of executive function (BRIEF/BRIEF-P). Children’s receptive vocabulary (PPVT-4) and global language skills (PLS-4/CELF-4) were also evaluated. Results The family environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
55
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 79 publications
(111 reference statements)
8
55
1
3
Order By: Relevance
“…On the parental report form from the BRIEF, the DHH group scored higher (indicating more problems) than the NH group, even though their scores were not within the clinically significant range. The DHH group had more behavior problems than the NH group across all of the scales, which is consistent with the previous research (Beer, Kronenberger, & Pisoni, 2011;Greiner, 2010;Hintermair, 2013;Holt, Beer, Kronenberger, Pisoni, & Lalonde, 2012;Pisoni, Conway, Kronenberger, Henning, and Anaya, 2010;Rhine, 2002). The analysis with individual scales revealed that the DHH group had significantly more problems than the NH group in the categories Initiate, Plan/Organization, and Monitor.…”
Section: Chapter 5 Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the parental report form from the BRIEF, the DHH group scored higher (indicating more problems) than the NH group, even though their scores were not within the clinically significant range. The DHH group had more behavior problems than the NH group across all of the scales, which is consistent with the previous research (Beer, Kronenberger, & Pisoni, 2011;Greiner, 2010;Hintermair, 2013;Holt, Beer, Kronenberger, Pisoni, & Lalonde, 2012;Pisoni, Conway, Kronenberger, Henning, and Anaya, 2010;Rhine, 2002). The analysis with individual scales revealed that the DHH group had significantly more problems than the NH group in the categories Initiate, Plan/Organization, and Monitor.…”
Section: Chapter 5 Discussionsupporting
confidence: 91%
“…The influence of age of implantation was also investigated and none of the EFs measures were correlated with age of implantation except the Tower subtest (r=0.132, p=0.470), which indicated that planning and organization abilities could be influenced by age of implantation. Holt, Beer, Kronenberger, Pisoni, and Lalonde (2012) investigated the relations between family environment and language development and EFs with 45 children with CIs. The EFs were measured using the BRIEF Parent Questionnaire, and language skills were measured using the PPVT-4 (Dunn & Dunn, 2007), the Preschool Language Scale (PLS, Zimmerman, Steiner, & Pond, 2002) and the CELF-4 (Semel, Wiig, & Secord, 2003).…”
Section: Children Who Are Dhh Language and Executive Functionsmentioning
confidence: 99%
“…However, deaf children who received cochlear implants (CIs), even those implanted at very early ages, often lag behind their peers with normal hearing (NH) in a range of speech and language standardized tests Geers, Strube, Tobey, Pisoni, & Moog, 2011;Holt, Beer, Kronenberger, Pisoni, & Lalonde, 2012;Houston & Bergeson, 2014). In addition, there is a considerable amount of variability in spoken language outcomes after cochlear implantation (Niparko et al, 2010).…”
mentioning
confidence: 99%
“…Recently, a growing body of evidence suggests that early auditory deprivation followed by degraded auditory input affects the development of the auditory neural pathway as well as other higher level cortical areas, which may have cascading effects for infants with CIs, who are processing already impoverished auditory input (Geers a et al, 2011;Holt et al, 2012;Pisoni & Geers, 2000). Indeed, recent studies suggest that deaf infants with CIs show differences in a range of cognitive skills as compared with their peers with NH, such as visual memory, procedural learning, and executive function Conway, Karpicke, & Pisoni, 2007;Houston & Bergeson, 2014;Pisoni, 2000).…”
mentioning
confidence: 99%
“…Yet outcomes after cochlear implantation for these children with associated disabilities, even if variable, show a positive evolution in speech perception, communication abilities, social engagement and quality of life [3,37]. Problematic family environments are significantly associated with poorer speech and language outcomes [9,38]. Then again, family factors such as a high socioeconomic level [5,35,39], sufficient parental involvement in the rehabilitation process [23,40,41] and higher levels of maternal education [42] are all related to improved language outcomes.…”
Section: Introductionmentioning
confidence: 99%